Medicinal plants used in traditional management of breast cancer: An ethnobotanical survey in Sidi Bel Abbès and Saïda, Northwestern Algeria - Benyamina, Abdelfettah; Soltani, Yamina; Toumi, Manel Nardjes; Toumi, Fawzia; Bouzidi , Mohamed Ali (Ethnobotany Research and Applications, 2026)
Background: Breast cancer is the most prevalent malignancy among women worldwide and represents a major public health challenge in Algeria. Despite advances in modern therapies, their limited accessibility and potential side effects lead many communities to continue relying on herbal remedies. Documenting this traditional knowledge is essential for preserving cultural heritage and identifying promising candidates for future pharmacological research. This study aimed to document the traditional use of medicinal plants for breast cancer management in northwestern Algeria, focusing on the wilayas of Sidi Bel Abbès and Saïda Methods: An ethnobotanical survey was conducted between 2023 and 2024 among 300 informants, using semi-structured interviews and free-listing techniques. Data were collected on plant species, parts used, and preparation methods. Botanical identification was confirmed using reference floras and specialized databases, and validated by taxonomic experts. Quantitative ethnobotanical indices, including Relative Frequency of Citation (RFC) and Use Value (UV), were applied to assess the cultural significance of the recorded species. Results: A total of 59 species belonging to 55 genera and 34 families were recorded. Herbs predominated (81%), with Lamiaceae, Amaranthaceae, and Apiaceae as the most represented families. Leaves (29%) and seeds (20%) were the most frequently used plant parts, while infusion (36%) and decoction (27%) were the dominant preparation methods. The most cited species included Ephedra alata Decne., Nigella sativa L., Allium sativum L., Curcuma longa L., and Berberis vulgaris L., alongside therapeutic uses of several less-documented taxa in the context of breast cancer treatment, such as Euphorbia officinarum L., Annona muricata L., and Hammada articulata (Moq.). Conclusion: This study provides the first comprehensive ethnobotanical documentation of medicinal plants used for breast cancer in northwestern Algeria. The results reveal both widely recognized and previously underreported species, highlighting the potential of local knowledge to inspire the discovery of novel therapeutic agents. Keywords: Ethnobotany; Breast cancer; Herbal medicine; Traditional knowledge; Lamiaceae; Northwestern Algeria.